A summary of previous investigations of the microgravity effects on bacterial virulence, infection and antibiotic resistance. (July 2022) - Wang, Chongzhen; Xing, Wanlin; Lu, Fan
Abstract: In the treatment of bacterial infections acquired during spaceflight, changes in bacterial virulence, infection process and antibiotic resistance under microgravity need to be taken into consideration. We therefore summarized previous investigations of the microgravity effects on bacterial virulence, infection and antibiotic resistance in this article. Some of the previous studies were carried out in microgravity environment during spaceflight, while others were carried out in simulated microgravity environment using rotating-wall vessel bioreactor or Rotary Cell Culture System. The results were that microgravity enhanced the virulence of certain bacterial strains and attenuated the virulence of certain bacterial strains, mitigated the severity of infection by certain bacterial strains, and enhanced the antibiotic resistance of certain bacterial strains and attenuated the antibiotic resistance of certain bacterial strains. Variation factors, such as bacterial strains (of same species) and exposure time, were discussed. The limitation of most of the previous spaceflight studies was a lack of an in-flight 1-g centrifuge control. In the investigation of the microgravity effects on bacterial virulence and infection, using non-mammalian animals is not as good as using mammalian animals to model human infection because there are many differences between mammals and non-mammalian animals. Our knowledge about the microgravity effects on bacterial infection and antibiotic resistance is far from completeness and future studies are needed. Highlights: The effects of microgravity on bacterial virulence, infection and antibiotic resistance were summarized. Variation factors, such as bacterial strains (of same species) and exposure time, were discussed. Limitations of some studies were indicated.